Improving Elementary Pre-Service Teachers' Science Teaching Self-Efficacy through Garden-Based Technology Integration - Erin Ingram; Trish Wonch Hill; Dena Harshbarger; Jenny Keshwani (MDPI AG, 2024)
School gardens and outdoor learning spaces are increasingly available to support authentic, student-centered exploration in the areas of science, technology, engineering, and mathematics (STEM). Integrating technology tools into school garden spaces in alignment with modern agricultural practices can support inquiry-based learning in which students engage in science practices such as collecting and analyzing data. However, educators currently lack the necessary knowledge, skills, and instructional support to enact technology-rich, garden-based STEM learning experiences. The Garden TOOLS program was designed to support teachers in leveraging technology to support inquiry-based teaching (IBT) in outdoor learning spaces. In this paper, we examine the impact of combining Garden TOOLS professional development workshops with lesson plan implementation in a practicum setting on elementary pre-service teachers' (PSTs) science teaching self-efficacy. We administered the STEBI-B pre- and post-intervention and assessed change in the STEBI-B subscales, personal science teaching efficacy (PSTE), and science teaching outcome expectancy (STOE). Participants included thirty-nine elementary PSTs enrolled in a 300-level science methods course in the rural Midwest. Garden TOOLS professional development workshop participants saw a statistically significant increase from pre- to post-workshop in their PSTE. Participants who also implemented the Garden TOOLS lesson showed both an increase in PSTE and STOE.